Abstract 028: Chronic Subdural Hematoma Treatment with Embolization Versus Surgery Study Protocol - Farhan Siddiq (Stroke: Vascular and Interventional Neurology)
Introduction Chronic subdural hematoma (cSDH) is one of the most common neurosurgical diseases with a significant financial burden. Current management includes observation for mild or asymptomatic patients and surgical drainage for moderate and severe patients. However, surgical drainage is associated with a 15% reoperation rate and a mortality of up to 10%. Middle meningeal artery embolization (MMAE) is a promising minimally invasive alternative with an estimated surgical recurrence rate of 6.8% and 4.6% for standalone MMAE and combined MMAE and surgery respectively. However, randomized data is lacking for this emerging therapy. Methods CHESS is a NIH‐funded, prospective, multi‐center, randomized, open label clinical trial. Subjects with moderately symptomatic cSDH (de novo or recurrent) will be randomized in a 1:1 radio to standalone MMAE or conventional surgery. Moderately symptomatic patients are defined as patients with moderate weakness (4/5), gait ataxia and/or mild aphasia. Embosphere or PVA will be used for MMAE. Primary outcome is defined as the proportion of patients that require rescue surgery or die within 180 days. Safety outcomes include the proportion of subjects with ischemic strokes, serious/life threatening adverse events, worsening neurological status or development of new disabling neurological symptoms, seizures, and cranial neuropathies (blindness and facial paralysis) within 180 days of randomization. One interim analysis for overwhelming efficacy and futility will be performed assuming a group sequential design of O’Brien and Fleming boundary. Results Based on an effect size of 13% of the composite primary outcome, a two‐sided Type I and Type II error of 0.05 and 0.15, and a dropout rate of 10%, a sample size of 394 patients is estimated. Conclusion CHESS will be the first US randomized controlled trial to provide evidence on the safety and effectiveness of 1) standalone MMAE vs surgical drainage; 2) particles as the embolic agent, and 3) MMAE on recurrent, in addition to de novo, cSDHs.